INTERPARLIAMENTARY INSTITUTIONS: CRITERIA AND CLASSIFICATION - A. A. Vinogradova (Сравнительная политика)
Abstract: Throughout the last two decades the scale of interparliamentary cooperation has grown substantially and such cooperation becomes increasingly institutionalised. The current article studies existing approaches to the structuration of the widening field of interparlaimentary organisations and international parliamentary assemblies and proposes its own complex classification.